Rad51 Expression in Nasopharyngeal Carcinoma and Its Association with Tumor Reduction: A Preliminary Study in Indonesia - Dian Cahyanti; Lisnawati Rachmadi; Vally Wulani; Marlinda Adham (Iranian Society of Pathology, 2016)
Background: Overexpression of Rad51 protein in many tumor cells has been proven to increase radioresistance and can be related to the resistance of chemosensitivity of tumor cells. This preliminary study was conducted to determine the relationship between the Rad51 expression level in nasopharyngeal carcinoma and the response of the treatment based on the measurement of the tumor reduction. Methods:Thirteen cases of the NPCs were analyzed. The expression levels of the Rad51 were examined from the pretreatment biopsies. Furthermore, tumor reductions were determined based on the change in sum longest diameter of the nasopharyngeal CT-scan before and after therapy. Results: The expression level of the Rad51 was associated with the reduction of tumor mass.       The P value was 0.049 and the correlation coefficient was 0.479. Conclusion:The tumor cells Rad51 expression levels may affect the tumor reduction of NPC after the therapy.